2000
DOI: 10.1046/j.1423-0410.2000.7920075.x
|View full text |Cite
|
Sign up to set email alerts
|

Gamma‐Ray‐Irradiated Red Blood Cells Stored in Mannitol‐Adenine‐Phosphate Medium: Rheological Evaluation and Susceptibility to Oxidative Stress

Abstract: The decreased deformability of gamma-ray-irradiated RBCs in MAP medium was mainly induced by dehydration due to potassium loss, and the membrane lipids and proteins were stably preserved against oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…1A-C, the increase in the external potassium concentration of RBC preparations was markedly enhanced by the irradiation, which is consistent with a previous report. 16) DPM, which is widely used in the treatment of cardiovascular disease, binds noncovalently with high affinity (K d ϭ 1.2 mM) to band 3, which is the most abundant protein on the RBC membrane with about a million copies per cell. 14) It has been reported that dipyridamole exerts an inhibitory effect on lipid peroxidation 17) and acts as a scavenger of superoxide anion, hydroxyl radical and peroxyl radical.…”
Section: Resultsmentioning
confidence: 99%
“…1A-C, the increase in the external potassium concentration of RBC preparations was markedly enhanced by the irradiation, which is consistent with a previous report. 16) DPM, which is widely used in the treatment of cardiovascular disease, binds noncovalently with high affinity (K d ϭ 1.2 mM) to band 3, which is the most abundant protein on the RBC membrane with about a million copies per cell. 14) It has been reported that dipyridamole exerts an inhibitory effect on lipid peroxidation 17) and acts as a scavenger of superoxide anion, hydroxyl radical and peroxyl radical.…”
Section: Resultsmentioning
confidence: 99%
“…As shown previously, the mechanical behavior of RBC is predominantly determined by cell shape, surface area-to-volume ratio, membrane and skeleton condition, and surface charge [1,2,3], properties that are altered during cold storage of RBC [4,5]. Cold storage of RBC in blood banks has been reported to be associated with changes in various RBC properties, including increased cell volume [6], oxidation of membrane protein and lipids [7], loss of cellular antioxidant capability [8], changes in K + and Na + concentration [9], changes in lipid in/out distribution on the RBC surface [8,10], and decreased cell membrane area [11,12]. Storage-induced damage to RBC, which can be noted as early as the second week of storage and progresses with storage duration [4], has been shown to impair the functionality of stored RBC (St-RBC) [5] and to facilitate their removal from circulation following transfusion [13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Erythrocyte deformability has become a focus of interest for surgeons [70,76] and transplantologists [17,49]. In transfusion medicine, assessment of RBC deformability [19,33] is a part of quality control.…”
Section: Introductionmentioning
confidence: 99%